2014
DOI: 10.1139/cjfr-2013-0427
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and genotype–environment interactions of Chinese fir (Cunninghamia lanceolata) in Fujian Province

Abstract: Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) is the most commercially important conifer in China, and the Nanjing Forestry University – Fujian Province Chinese fir Cooperation (NJFU – Fujian Cooperation) breeding program has advanced it into the third cycle of selection and breeding. In this paper, we estimated genetic parameters from four sites for 80 half-sib families and summarized previous estimates of genetic parameters in Chinese fir with an objective to propose optimal breeding strategy. Heritabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
1
21
0
5
Order By: Relevance
“…Bian et al [12] reported that the Chinese fir repeatability of H, DBH and WBD traits in clonal tests ranged from 0.63-0.79, 0.49-0.78, and 0.51-0.75, respectively. Our report showed a high estimated repeatability for these traits (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bian et al [12] reported that the Chinese fir repeatability of H, DBH and WBD traits in clonal tests ranged from 0.63-0.79, 0.49-0.78, and 0.51-0.75, respectively. Our report showed a high estimated repeatability for these traits (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other conifer breeding programs around the world, the improvement of Chinese fir mainly emphasizes the enhancement of growth and adaptability with the following activities: provenance testing, plus-tree selection, establishment of breeding garden/gene bank, family/progeny (half-sib and full-sib) and clonal testing, parent tree (plus-tree clone) reselection, clonal seed orchard establishment, and so forth [12]. Wood quality traits were recently targeted as a breeding objective due to increasing demands for high-quality timber in the last 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…H, height; DBH, diameter at breast height; V, stem volume; WBD, wood basic density; Hy, hygroscopicity; HR, heart-wood ratio; TL, tracheid length; TD, tracheid diameter; TLDR, tracheid length-diameter ratio; SD, standard deviation; F, the ANO-VA (analysis of variance) parameter F (*p < 0.05, **p < 0.01); CV, coefficient of variation; R, repeatability tions in southern China (Shi et al 2010). Based on the knowledge and availability of genetic variability for selection (Bian et al 2014), remarkable successes in breeding have already been achieved for this species, e.g. large-scale collection of elite germplasms, establishment of first and second and third generation seed orchards, and significant gains of superior clones.…”
Section: Introductionmentioning
confidence: 99%
“…The incomplete block design was generally effective in Fujian's hilly Chinese fir sites. These sites typically have environmental gradients from hill top to bottom (Bian et al 2014). To reduce this global trend of environmental variation, blocks were usually employed along the contour of the site to keep the microenvironment within the same block as homogeneous as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding for growth traits in the first two generations has increased average growth rate by almost 30% (Shi 1994). In a quantitative genetics survey, several unusual and interesting unique genetic properties of Chinese fir's breeding population such as low heritability of wood density and low negative genetic correlation between growth and wood density, a large difference between narrow-sense and broad-sense heritability, and regional-related G by E interactions were found (Bian et al 2014). Several relatively large progeny trials with a family of sufficient size for genetic analyses revealed low heritability for DBH (e.g., h 2 = 0.09 in a trial of 112 families (Fang and Shi 1998); h 2 = 0.05 in another trial of 228 families (Yu et al 2001)).…”
Section: Introductionmentioning
confidence: 99%